Dental caries experience and treatment needs of institutionalized mentally challenged and normal children of age group 6-13 years in Mysore city - Vinayaka Konakeri; Darshana Bennadi; Maurya Manjunath; C.V.K Reddy (Wolters Kluwer Medknow Publications, 2016)
Introduction: Dental negligence is very common among mentally challenged children. That might be due to their condition makes it difficult to maintain good general and oral health and so their dentition may be ravaged by dental problems. Aim: To assess and compare the dental caries experience and treatment needs of institutionalized mentally challenged and normal children of age group 6-13 years in Mysore. Materials and Methods: A descriptive cross-sectional study was conducted among institutionalized mentally challenged and normal children of age group 6-13 years in Mysore. Modified World Health Organization proforma and predesigned questionnaire to assess dental caries experience and treatment needs. Results: Means number of decayed, extracted, filled teeth and decayed, extracted, filled surface score was higher among mentally challenged compared to normal children. The findings were found to be statistically highly significant (P < 0.001). The mean number of decayed missing filled teeth and decayed missing filled surface score for mentally challenged and normal children in relation to gender were statistically significant (P < 0.05). Temporomandibular joint problems and dentofacial anomalies were common among mentally challenged children compared to normal children. Conclusion: Health professionals should, therefore, be aware of the impact of mental illness and its treatment on oral health, health personnel should receive training to support and provide all possible services to this population.